Step 1

Solution:

Consider the given expression is

\(s^{2}-10st+25t\)

Here, -10 st can be factorized into -5st and -5st that is

\(s^{2}-10st+25t=s^{2}-5st-5st+25t\)

\(s^{2}-5st-5st+25t=s(s-5t)-5t(s-5)\)

\(s^{2}-10st+25t=s(s-5t)-5t(s-5)\)

Step 2

This is the required prime factor of the given expression.

Solution:

Consider the given expression is

\(s^{2}-10st+25t\)

Here, -10 st can be factorized into -5st and -5st that is

\(s^{2}-10st+25t=s^{2}-5st-5st+25t\)

\(s^{2}-5st-5st+25t=s(s-5t)-5t(s-5)\)

\(s^{2}-10st+25t=s(s-5t)-5t(s-5)\)

Step 2

This is the required prime factor of the given expression.